The Impact of Raising Cows and Buffaloes Inside the House toward Human Health (Public Health Perspective Journal, 2020)
Indonesia is a country that has great potential in the field of animal husbandry which is very important as a support for the supply of animal protein derived from livestock. Cows and Buffaloes are livestock that have economic potential, diseased livestock have a very negative impact on humans. Diseases in livestock can be transmitted quickly and can be fatal, namely death. These diseases can arise caused by bacteria, viruses, fungi, and parasites. It turns out that cows disease is also experienced by pre-weaning calves, health problems caused by two factors, namely infectious factors include bacteria, viruses, protozoa, and parasites, as well as non-infectious factors in the form of management and environmental factors. Health problems that often occur are diarrhea, umbilical cord infections, bloating, intestinal worms, and pneumonia. Infectious diseases that can be transmitted from livestock to humans are so many, but still relatively little is known by the general public, so when one of the infectious diseases of livestock occurs in the community what happens is not the proper attitude and action but panic and worries that spread . Knowledge about diseases transmitted by livestock, symptoms, and appropriate prevention and treatment is still limited. The purpose of this study is to analyze the relationship between risk factors and health effects of raising cows and buffaloes in the house with various diseases that arise in Jraganan Village, Bodeh District, Pemalang Regency. This research is an observational analytic study with cross-sectional approach. The selected population is all residents of Jraganan Village who maintain buffaloes and cows in the house. Examples in this study were 51 respondents who included cows and buffalo breeders who kept livestock in the house. The results showed that there was a significant relationship between farmers raising cows and buffaloes in the house with contracting livestock diseases such as itching and diarrhea in Jraganan Village, Bodeh District in 2016. Respondents with the risk of contracting the disease were 51 people (53.12%). The results of the study concluded that cage in the house has a higher risk of contracting diseases from livestock to humans, namely skin diseases and diarrhea. Diarrhea and skin diseases in cows, especially cows, are not a disease, but rather are clinical signs or symptoms of a more complex disease that can be caused by various things.